BRAINSTORMING DINI DENGAN ORIGAMI UNTUK ANAK-ANAK - Zaki Ainul Fadli; Nur Hastuti; Maharani Patria Ratna; Arsi Widiandari; Dewi Saraswati Sakariah (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
(Title: Early Brainstorming With Origami For Children) The purpose of this paper is to uncover the usefulness of origami as an effective way of early brainstorming for children. The method used is to involve the children in the origami training activities as a form of community service. Training is not done in the usual way, but done principally on the four basic brainstorming guidelines so that the nature of the training is not up-bottom but bottom-up. This principle is not done strictly considering the participants are children. This means that mentor involvement is still needed to encourage participants to come up with ideas on how to fold the paper and shape it into the intended shape effectively and efficiently. The result of this training is origami can be an alternative way in improving creativity and courage of children in expressing ideas.